Corporate Social Responsibility-Based Teaching Factory as a Strategy for Enhancing Vocational High School Graduate Competence - Zalma Niendya Pangestika; Dian Khoiriyani Putri; Kamal Ramadhani; Afif Nur Khayati; Joko Widodo (Ilmu Inovasi Nusantara, 2026)
Corporate Social Responsibility (CSR) programs play a strategic role in ensuring that companies contribute not only to economic growth but also to social development, particularly in the education sector. One of the challenges faced by vocational schools is the gap between graduates’ competencies and industry needs, which often results from limited facilities, weak industry linkages, and curricula that are not fully aligned with professional demands. To address this issue, the Djarum Foundation implements an education-oriented CSR program in collaboration with SMK PGRI 2 Kudus and industry partners through the Teaching Factory model. This study aims to analyze the implementation of the Teaching Factory program at SMK PGRI 2 Kudus and to examine the collaboration patterns among the school, the Djarum Foundation, and industry partners in enhancing the quality of vocational education. This study employs a descriptive, qualitative approach, utilizing observation, documentation, and in-depth interviews. Interview guidelines focus on collaboration mechanisms among stakeholders, the implementation model of the Teaching Factory program in the culinary department, the curriculum framework applied, and the availability of learning facilities and infrastructure. Data were analyzed using Miles and Huberman's interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the CSR collaboration between the Djarum Foundation and SMK PGRI 2 Kudus has a significant positive impact on producing competent and competitive graduates. CSR contributions include the construction of Teaching Factory facilities, teacher capacity building, provision of practical equipment and infrastructure, and reinforcement of an industry-based curriculum. The synergy among the school, industry, and the Djarum Foundation has been well established, enabling students to gain hands-on experience and better prepare them for the professional work environment. The study implies that education-focused CSR programs can serve as an effective strategy for strengthening vocational education and human resource development. It also suggests that other corporations should emulate the Djarum Foundation’s model to support sustainable partnerships between the education and industry sectors